Electric-Field Nanobubble-Enhanced Progress in Anaerobic Digestion Unit Operations: Biogas Upgrading and Up- and Down-Stream Water and Sludge Treatment Operations - Niall J. English (Nanomaterials)
An integrated approach is sorely needed to treat biogas emanating from anaerobic digesters (AD) which is cost-effective, in terms of upgrade/purification to ~95–98% methane needed for pipeline injection. This is a very pressing environmental and waste-management problem. At present, biogas water-/solvent-washing operations require significant capital investment, with high operational and maintenance costs. In the present study, we deployed a facile and efficient novel nanobubble-formation approach using applied electric fields to boost biogas-enrichment operations: we achieve substantial methane enrichment via selective CO2 and H2S take-up in water in the form of nanobubbles. This enables an integrated waste-processing vision using cutting-edge engineering-science advances, and making anaerobic digestion a circular-economic and practical reality, that can be deployed at scale—initially developing at the small scale—and points the way for low-energy CO2 capture in the form of nanobubbles by dint of the electric-field approach. In addition, we carried out nanobubble generation using various gases for water treatment for both up- and down-stream sludge-containing (waste)water, achieving meaningful operational successes in AD operations and organic-fertiliser production, respectively.